PEMANFAATAN HASIL HUTAN BUKAN KAYU OLEH MASYARAKAT SEKITAR HUTAN DESA MINANGA III KABUPATEN MINAHASA TENGGARA - Christien N. Kendek; Johny S. Tasirin; Reynold P. Kainde; Josephus I. Kalangi (Universitas Sam Ratulangi, 2013)
ABSTRACTThe utilization of the non-timber forest crop by the people who are living in the forest area, was studied. Interview by giving samples to as many as 30 people, which has been taken from the overall population 95 families.This research was done on November to december 2011. The result was indicating that the rest of minor societies around 20% are depending their life on the non timber forest crop.First, some of them are the roof maker by using the palm tree leaves as the row material, second some of them are the traditional medicines (herbs) maker by using plants or trees in the forest as ingredients. Third some of them are the wood fishing such as : crabs, shells, and stream fishes.Non-timber forest crop that provide the greatest revenue is income from crab seekers which can give an income of Rp 47,160,000/year. As for the whole, the value of the economic benefit of non-timber forest crop to the local community is rp 83,855,000/year obtained from the utilization of Nypa fruticans and foodstuff as such as shells, crabs and stream fishes.The Key Words: Non Timber Crop, Questioner Catalogue, Samples, Palm Trees, Wood Fishes.